Myelosuppression and Nephrotoxicity Induced by Cisplatin in Female Rats: The Role of Berberine Nanoparticles - Mohamed, Nema Abdelhameed (JOURNAL OF ADVANCES IN BIOLOGY, 2018)
Cisplatin (CDDP) is one of the most effective antineoplastic drugs used in chemotherapy, strategies to protect tissues against cisplatin nephrotoxicity is a clinical interest. This study aimed to evaluate the possible protective effect of berberine nanoparticles (BBR-NPs) against cisplatin-induced nephrotoxicity in female rats. Intraperitoneal (IP) injection of cisplatin (8 mg/kg) caused significant decrease in RBC, Hb, Hct, WBC and platelets. Also, cisplatin caused disturbances in kidney function as documented by a significant increase in urea, uric acid, creatinine and MDA, with significant decreases in the total protein, albumin, GSH and total thiol.TNF- , caspase-3, IL-2, IL-6 and IL-1 were increased in cisplatin treated group. The histopathological changes in cisplatin group include degeneration and desquamation of tubular epithelial cells, hyaline cast formation, inflammatory cell infiltration and tubular dilation. Oral administration of BBR-NPs at a dose 1mg/kg/day for 30 days after cisplatin produced significant decrease in the levels of urea, uric acid, creatinine, TNF- and caspase-3 as well as kidney MDA with a marked increase in total protein, albumin, GSH, total thiol and repairing the histopathological changes. Scanning microscope of RBC showed the protective effect of BBR-NPs against the different changes induced by CDDP. The present study suggested that the anti-oxidant and anti-inflammatory effects of BBR-NPs may prevent CDDP-induced nephrotoxicity via decreasing the oxidative stress, inhibiting the inflammation and apoptosis.